A facile route to prepare dimeric BODIPY-based porous organic polymers using FeCl3. (6th June 2017) - Wang, De-Gao; Song, Fan; Tang, Hui; Jia, Xin-Ru; Song, Min; Kuang, Gui-Chao
Abstract : A facile FeCl3 catalyzed oxidation of the dimeric BODIPY monomers with different spacers to construct porous organic polymers have been reported. These polymers' singlet oxygen generation capacities are dependent on the spacers. Abstract : Herein, we report a facile FeCl3 -catalyzed oxidation reaction of dimeric BODIPY monomers with different spacers to construct porous organic polymers. The singlet oxygen generation capacities of these polymers are dependent on the spacers.